2016
DOI: 10.1038/srep21543
|View full text |Cite
|
Sign up to set email alerts
|

Cesium adsorption/desorption behavior of clay minerals considering actual contamination conditions in Fukushima

Abstract: Cesium adsorption/desorption experiments for various clay minerals, considering actual contamination conditions in Fukushima, were conducted using the 137Cs radioisotope and an autoradiography using imaging plates (IPs). A 50 μl solution containing 0.185 ~ 1.85 Bq of 137Cs (10−11 ~ 10−9 molL−1 of 137Cs) was dropped onto a substrate where various mineral particles were arranged. It was found that partially-vermiculitized biotite, which is termed “weathered biotite” (WB) in this study, from Fukushima sorbed 137C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(74 citation statements)
references
References 27 publications
5
69
0
Order By: Relevance
“…Furthermore, one can see that 5-10 min is enough to achieve adsorption equilibrium under the experimental conditions used in this study, which indicates that physical adsorption rather than ion exchange contributes mainly to the removal of metal ions by natural and synthetic allophane adsorbents. This finding is in line with previous experimental results, where allophane has been successfully used in the remediation of aqueous solutions that were contaminated with, for example, heavy metals cations [15,22,33,35], metal (oxy)anions [18,23,30], heterocyclic organic components [10] and anionic surfactants and organic acids [17,23]. …”
Section: Effect Of Contact Time On the Adsorption Kinetics Of Aqueoussupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, one can see that 5-10 min is enough to achieve adsorption equilibrium under the experimental conditions used in this study, which indicates that physical adsorption rather than ion exchange contributes mainly to the removal of metal ions by natural and synthetic allophane adsorbents. This finding is in line with previous experimental results, where allophane has been successfully used in the remediation of aqueous solutions that were contaminated with, for example, heavy metals cations [15,22,33,35], metal (oxy)anions [18,23,30], heterocyclic organic components [10] and anionic surfactants and organic acids [17,23]. …”
Section: Effect Of Contact Time On the Adsorption Kinetics Of Aqueoussupporting
confidence: 92%
“…≡Al-OH° and ≡Si-OH°) in adsorbents are favorable to ensure a desired adsorption rate and appropriate metal ion removal efficiency [10,11]. Recently, agricultural and industrial waste products, activated carbon nanotubes, cellulose, carbonates, Feand Al-oxyhydroxides, zeolites, phosphates and clay minerals are used in the remediation of water that is severely polluted with persistent and hazardous components such as heavy metal ions, dyes, antibiotics, biocide compounds and other organic chemicals [12][13][14][15][16]. The use of clay minerals for wastewater treatment can be advantageous over other sorbents due to their worldwide occurrence, low mining and processing costs and outstanding physicochemical and surface properties, making clayey materials suitable for selective ion exchange, adsorption and catalyst uses [1,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, one can see that 5-10 min is enough to achieve adsorption equilibrium under the experimental conditions used in this study, which indicates that physical adsorption rather than ion exchange mainly contributes to the removal of metal ions by natural and synthetic allophane adsorbents. This finding is in line with previous experimental results, where allophane has been successfully used in the remediation of aqueous solutions that were contaminated with, for example, heavy metals cations [15,22,33,35], metal (oxy)anions [18,23,30], heterocyclic organic components [10], anionic surfactants, and organic acids [17,23]. Unfortunately, in most of these works, high reaction times (e.g., 24 h or longer) have been used and no kinetic data are provided [10,15,18,22,23,30,35], which greatly complicates the comparison of the adsorption kinetics of, for example, allophanic soils and synthetic allophanes.…”
Section: Effect Of Contact Time On the Adsorption Kinetics Of Aqueoussupporting
confidence: 82%
“…4,21) RADIOISOTOPES mica core and vermiculite structure in a particle of micaceous minerals. 7) Mukai et al (2016) 15) found that partially-vermiculitized biotite (weathered biotite) sorbed RCs far more than the other clay minerals such as fresh biotite, illite, smectite, kaolinite, halloysite, allophane, and imogolite, on the same substrate. In addition, the sorbed RCs in the weathered biotite was hardly leached with 0.1 mol dm −3 hydrochloric acid.…”
Section: Introductionmentioning
confidence: 99%